Geophysical investigation for Copper-Sulphide ore at Dhusa, Nepal (Journal of Nepal Geological Society, 1982)
Self-Potential, Induced Polarisation and Magnetic Surveys conducted in an anomalous zone delineated by preliminary to advanced stages of geochemical exploration showed good correlation with the geochemical anomaly. SP and IP survey conducted have a very limited depth of investigation. Qualitative interpretation of SP curves clearly indicated the existence of two faults, whereas combined results of SP and IP showed weathered and "deep seated" (30m) polarizable body. The magnetic survey did not give any significant result.Three bore holes drilled in the best geophysical, geochemical anomaly zone intersected mineralization of chalcopyrite chalcocite and pyrite with an average grade of 0.17% Cu over 38m true thickness. The post drilling IP and resistivity sounding conducted at 10 points along a line passing through one of the drill holes indicated the possibility of better mineralization further down dip. The mineralization is expected to be present in the form of lenses.